In great company how to spark peak performance by creating an emotionally connected workplace - Carter, Louis (McGraw-Hill Education, 2019)
Drive long-term profits and growth by making the company a place your employees love. In Great Company presents a practical approach to ensure that your employees perform at their highest possible levels. It's not about increasing salaries, offering huge bonuses, or investing in the latest employee engagement tools. The real answer is simpler, deeper, and longer-lasting: getting your people to love where they work. Founder and CEO of one of today's top leadership development firms, Best Practices Institute, Louis Carter takes you step by step through the process of building a lasting emotional connection between your staff and your company. Carter's proven strategy is founded on five key principles: collaboration, optimism, values, respect, and performance. Fuse them together, and your company will be the envy of your industry. This groundbreaking guide provides everything you need to create an environment where people have a strong sense of belonging-a place where people finally feel like they're part of something big, where employees want to work collaboratively and creatively, where your staff and your company grow together. Bridge the engagement gap by ensuring that every member of your team spends their entire work day in great company.
Includes bibliographical references and index. - Print version record
Keywords: Organizational behavior; Emotional intelligence; Employee motivation; Corporate culture; Comportement organisationnel; Intelligence émotionnelle; Personnel; Motivation; Culture organisationnelle